Schisandrin C targets Keap1 and attenuates oxidative stress by activating Nrf2 pathway in Ang II‐challenged vascular endothelium. (10th January 2019) - Han, Jibo; Shi, Xiaowen; Du, Yao; Shi, Fengjie; Zhang, Bin; Zheng, Zhanxiong; Xu, Jianjiang; Jiang, Liqin
Abstract : Vascular endothelial dysfunction plays a crucial role in the pathogenesis of cardiovascular diseases. Oxidative stress is a key pathophysiological mechanism underpinning endothelial dysfunction. Schisandrin C (Sch C), a dibenzocyclooctadiene derivative of Schisandra chinensis, has antioxidative properties. Here, we report the use of Sch C as a novel therapeutic for the treatment of angiotensin II (Ang II)‐induced endothelial deficits and explore the underlying mechanisms and the target of Sch C. Our results demonstrated that Sch C treatment prevents aorta oxidative stress and improves relaxation in mice, challenged with subcutaneous infusion of Ang II. In addition, Sch C significantly ameliorates Ang II‐induced oxidative stress in rat aortic endothelial cells. We then discovered that these antioxidative effects of Sch C are mediated through the induction of nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2). Using an expression plasmid and molecular docking, we identified that Kelch‐like ECH‐associated protein‐1 (Keap1), a negative regulator of Nrf2, is a target of Sch C. These findings provide evidence for the potential use of Sch C as an antioxidative agent for treatment of vascular endothelial deficits.